PENGARUH PEMBERIAN MADU TERHADAP DIARE PADA REMAJA DI ASRAMA AS’ADIYAH PONDOK PESANTREN DARUL’ULUM JOMBANG - Nisa, Nurul Khoirun; Khotimah, Khotimah; Zuliani, Zuliani (Jurnal EDUNursing, 2020)
Abstract Diarrhea is still a major cause of morbidity and mortality at all ages. Diarrhea is a complaint that is often found in adults. Honey is a natural liquid derived from plant nectar produced by honey bees, as a drug with millions of benefits it has been known since ancient times. This study aims to analyze the effect of honey treatment on diarrhea in adolescence. The research design in this study used Quasy Experimental Design (quasi experimental design) with Control Time Series Design. Determination of samples using consecutive sampling, with a sample size of 16 respondents, while the variables studied were honey and diarrhea. This research was conducted at the age of adolescents at the As'adiyah Dormitory of the Darul ‘Ulum Jombang Islamic Boarding School. Methods of data collection with observation sheets and data obtained were analyzed by repeated measures statistical test with significance α <0.05. Whereas from the computerized test results it was found that α = 0.013 based on the consistency of BAB and α = 0.001 based on BAB frequency which means that there is an effect of giving honey to diarrhea in adolescents. The results of this study show that honey treatment is effectivel to  diarrhea in adolescents. Thus the next researcher can develop and continue to need to look for other factors related to diarrhea by expanding the sample and using questionnaires or observation sheets and in processing other data. Keywords: Diarrhea, Honey treatment, Adolescents in As’adiyah dormitory